2022
DOI: 10.1186/s12944-022-01743-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between combined exposure to plasma heavy metals and dyslipidemia in a chinese population

Abstract: Background Exposure to heavy metals in the environment is widespread, while the relationship between combined exposure to heavy metals and dyslipidemia is unclear. Methods A cross-sectional study was performed, and 3544 participants aged 30 years or older were included in the analyses. Heavy metal concentrations in plasma were based on inductively coupled plasma‒mass spectrometry. The relationship between heavy metals and dyslipidemia was estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…In addition, different types of blood cells play different roles in the systemic inflammatory response. Moreover, based on the results of previous studies conducted by the group, a correlation between the presence of heavy metals and a variety of diseases was found in our study participants [ 20 22 ], which are closely related to inflammation [ 31 , 32 ]. Meanwhile, metal exposure induces an inflammatory response in the organism, which is manifested by different degrees of changes in blood cell levels [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In addition, different types of blood cells play different roles in the systemic inflammatory response. Moreover, based on the results of previous studies conducted by the group, a correlation between the presence of heavy metals and a variety of diseases was found in our study participants [ 20 22 ], which are closely related to inflammation [ 31 , 32 ]. Meanwhile, metal exposure induces an inflammatory response in the organism, which is manifested by different degrees of changes in blood cell levels [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 68%
“…Hypertension was defined as one or more of the following conditions or currently taking antihypertensive medication: systolic blood pressure ≥ 140 mmHg and/or diastolic blood pressure ≥ 90 mmHg [ 28 ]. Dyslipidemia was defined as one or more of the following conditions and/or taking lipid-lowering medications: total cholesterol ≥ 6.22 mmol/L, triglycerides ≥ 2.26 mmol/L, low-density lipoprotein cholesterol ≥ 4.14 mmol/L, and high-density lipoprotein cholesterol < 1.04 mmol/L [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are still deficiencies. First, as a cross-sectional study, we could not elucidate the causal relationship between PAH exposure, telomere length, and dyslipidemia; second, dyslipidemia may also be influenced by other factors such as heavy metals, 40 high temperature, 41 and noise 42 due to the specificity of the working environment of coal miners. However, our study did not consider these occupational factors that may have an impact on the outcome; finally, the subjects were selected from a single coal mine in Shanxi Province, so the findings may not be generalizable; therefore, further exploration and validation through a large sample cohort study are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Additional epidemiological studies have found an association between body As burden and the risk of dyslipidemia and atherosclerosis [ 166 , 167 ]. In agreement with these epidemiological data, laboratory findings demonstrated an adverse effect of As exposure on serum lipid profile, characterized by reduced HDL-C and increased circulating TC, TG, and LDL-C concentrations [ 168 ].…”
Section: Introductionmentioning
confidence: 99%